Podroz do Wloch, Sycylii i Malty - Wiszniewski, Michal, 1794-1856.; Barycz, Henryk (Warszawa : Panstwowy Instytut Wydawniczy, 1982)
An account of travels in Italy, Sicily and Malta in the early 19th century by a Polish traveler.
Includes indexes.
Keywords: Wiszniewski, Michal, -- 1794-1856.; Italy -- Description and travel; Sicily (Italy) -- Description and travel; Malta -- Description and travel